Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.7717/peerj.9982
|View full text |Cite
|
Sign up to set email alerts
|

Development of a noninvasive photograph-based method for the evaluation of body condition in free-ranging brown bears

Abstract: Body condition is an important determinant of health, and its evaluation has practical applications for the conservation and management of mammals. We developed a noninvasive method that uses photographs to assess the body condition of free-ranging brown bears (Ursus arctos) in the Shiretoko Peninsula, Hokkaido, Japan. First, we weighed and measured 476 bears captured during 1998–2017 and calculated their body condition index (BCI) based on residuals from the regression of body mass against body length. BCI sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 16 publications
(27 citation statements)
references
References 53 publications
0
25
0
Order By: Relevance
“…Previous studies of bears have shown cyclical annual patterns in body condition: declining through spring to summer, beginning to increase concomitantly with the onset of high-energy food consumption, and then peaking before hibernation (Hilderbrand et al 2000;McLellan, 2011;Schwartz et al 2014). In our study area, although data were available for only one individual, a seasonal fluctuation in body condition was reported from late June to early October, with the lowest condition in late August and the highest in early October (Shirane et al 2020).…”
Section: Introductionmentioning
confidence: 53%
See 4 more Smart Citations
“…Previous studies of bears have shown cyclical annual patterns in body condition: declining through spring to summer, beginning to increase concomitantly with the onset of high-energy food consumption, and then peaking before hibernation (Hilderbrand et al 2000;McLellan, 2011;Schwartz et al 2014). In our study area, although data were available for only one individual, a seasonal fluctuation in body condition was reported from late June to early October, with the lowest condition in late August and the highest in early October (Shirane et al 2020).…”
Section: Introductionmentioning
confidence: 53%
“…Following Shirane et al (2020), we assessed the body condition of adult female brown bears using morphometric measurements from photographs. Shirane et al (2020) confirmed that this method accurately reflects true body condition (i.e., the body condition index obtained from the regression of body mass against body length) and has high measurement precision between photographs. However, this photograph-based method is limited by its requirement for photographs with sufficient quality for morphometric measurements and bear posture that does not affect the evaluation.…”
Section: Estimation Of Body Conditionmentioning
confidence: 99%
See 3 more Smart Citations